Organizational Readiness, Behavior, and Public Value Creation in Government Services: Kesiapan Organisasi, Perilaku, dan Penciptaan Nilai Publik dalam Layanan Pemerintah - Marwan Sabah Hasan; Omar Khazaal Khudhair; Dr.Mustafa Abdullah Hasan (Academia Open, 2025)
General Background: Public organizations in developing countries face mounting pressures to improve service quality, transparency, and legitimacy. Specific Background: Iraq’s electricity sector exemplifies this challenge, where persistent service failures have eroded citizen trust and highlighted the need for organizational reform. Knowledge Gap: Although prior research has examined organizational readiness, behavior, and public value separately, little is known about how readiness translates into citizen-centered outcomes through employee behaviors in fragile governance contexts. Aims: This study investigates how organizational readiness influences public value creation in the Iraqi Ministry of Electricity, with organizational behavior as a mediating factor. Results: Using survey data from 120 employees and mediation analysis, findings show that readiness dimensions—leadership commitment, resource availability, and change efficacy—significantly enhance public value. This relationship is partially mediated by organizational behavior, particularly organizational citizenship and innovative work behaviors. Novelty: The study integrates readiness theory with public value governance, offering a comprehensive framework that links structural readiness with discretionary employee actions. Implications: The results provide actionable insights for policymakers, emphasizing the importance of strengthening leadership support, resource sufficiency, and a culture of innovation to restore citizen trust and improve public sector outcomes in Iraq.Highlight : Readiness plays an important role in enhancing public value. Organizational behavior is the main mediator. Leadership commitment and change efficacy are the most influential factors. Keywords : Organizational Readiness, Organizational Behavior, Public Value Creation, Leadership Commitment, Change Efficacy